Studies on Oberonia 3. Aberrant flowers and other floral modifications in the orchid genus Oberonia - Geiger, Daniel L.; Kocyan, Alexander (Nordic journal of botany, 2018)
Orchid flowers are amongst the most conspicuous attractions that plants have generated over evolutionary epochs. However, organ homology in particular of androecium and gynoecium of orchid flowers have been, and are still, the subject of long‐term discussion. Studies of aberrant – teratologic – flowers have traditionally helped to clarify organ identity in orchids. We here present for the first time teratological flowers within the florally smallest and inconspicuous orchid genus Oberonia and illustrate them by light and scanning electron microscopy. Pseudopeloria with half of a lateral petal transformed into a lip was found in O. costeriana J.J.Sm. and O. mucronata (D.Don) Ormerod & Seidenf. A supernumerary lip is known from O. mucronata. Oberonia rufilabris Lindl. is documented with multiple aberrations: triple gynostemium and a total of 10 tepals, twin flowers, and duplicate lips. We interpret these aberrations in light of known floral developmental and organ identity information.